Phospholipase A2 enzymes differently impact PUFA release and oxylipin formation ex vivo in rat hearts. (April 2023) - Manson, Anne; Winter, Tanja; Aukema, Harold M.
Highlights: sPLA2 enzymes mediate DHA release and oxylipin formation in rat hearts. iPLA2 enzymes are likely responsible for other PUFA release and oxylipin formation. COX and 12-LOX oxylipins were resistant to inhibition by PLA2 inhibitors. Oxylipin formation does not necessarily reflect PUFA release. Abstract: Phospholipase A2 (PLA2 ) enzymes cleave cell membrane phospholipids and release polyunsaturated fatty acids (PUFA), which can be converted into oxylipins. However, little is known about PLA2 preference for PUFA, and even less is known about how this further impacts oxylipin formation. Therefore, we investigated the role of different PLA2 groups in PUFA release and oxylipin formation in rat hearts. Sprague-Dawley rat heart homogenates were incubated without or with varespladib (VAR), methyl arachidonyl fluorophosphonate (MAFP) or EDTA. Free PUFA and oxylipins were determined by HPLC-MS/MS, and isoform expressions by RT-qPCR. Inhibition of sPLA2 IIA and/or V by VAR reduced the release of ARA and DHA, but only DHA oxylipins were inhibited. MAFP reduced the release of ARA, DHA, ALA, and EPA, and the formation of ARA, LA, DGLA, DHA, ALA, and EPA oxylipins. Interestingly, cyclooxygenase and 12-lipoxygenase oxylipins were not inhibited. mRNA expression levels of sPLA2 and iPLA2 isoforms were highest whereas levels of cPLA2 were low, consistent with activity. In conclusion, sPLA2 enzymes lead to the formation of DHA oxylipins, while iPLA2 is likely responsible for the formation of most other oxylipins in healthy rat hearts. Oxylipin formation cannot be implied from PUFA release, thus, both should be evaluated in PLA2 activity studies.